Should Title VII of the United States Code Prohibiting Sex Discrimination Be Based on Sexual Orientation: An Argument - Andrew J. Schatkin (Academicus International Scientific Journal, 2020)

(untitled)
The article considers the issue of what is sex and sexual orientation discrimination and  should under the federal statute 2000 Esexual orientation be encompassed under the term sex. The statute has long been intrepreted as directed to physical sex and not read as including sex orientation as an aspect of sex. The article however traces and identifies a clear trend in the federal court system of the United States to interpreting  and  includng sexual orientation or homosexuality and lesbianism within this statute’s prohibition against traditional sex discrimimation. The author holds the view  that homosexuality and sexual orientation should be given the same and equal protection as sex discrimimation in the federal courts of the United States and in time this statute will rightly be interpreted not only to include sex discriminataion as directed in its tradidtional understanding but be analayzed and interpreted to include protection against sexual orientation discrimination.